A rare case of intrahepatic gallbladder in the setting of penetrating liver injury, a retrospective diagnosis: a case report - Kopperundevi, V.; Prabhakar, Joyce; S. L., Samarthan; Kannan, R. (International Surgery Journal, 2022)
Intrahepatic gallbladder is a rare congenital variant among the ectopic gallbladder. Inadequate preoperative imaging studies might mislead the surgeon and most of the times can create unnecessary complications in the setting of cholecystectomy. Often these anomalies are either picked up intraoperatively or by retrospective diagnosis. Patients usually are at a high risk for developing cholelithiasis due to abnormality in the contractile ability of the gallbladder. The clinical symptoms can be misleading to many of the clinicians as recurrent dull aching right upper abdominal pain for many years, treated for acute peptic disease and dyspepsia.